Patient reported self‐help strategies and the perceived benefits for managing sub‐threshold depressive symptoms: A nested qualitative study of Australian primary care attendees. (12th November 2021) - Taylor, Anna Kathryn; Palmer, Victoria J.; Davidson, Sandra; Fletcher, Susan; Gunn, Jane
Abstract: Background: Subthreshold depression is common in primary care, but there is little information about the self‐help strategies that patients use and the perceived benefits of these. Aim: This study sought to elicit the self‐help strategies that primary care attendees identified as beneficial for the self‐management of subthreshold depressive symptoms and the implications for general practitioners. Method: Semi‐structured telephone interviews were conducted with 14 people (April–May 2017) from the Target‐D randomised controlled trial (RCT). Target‐D investigated whether using a patient‐centred clinical prediction tool and an e‐health platform to match mental health management options to prognosis was beneficial for improving depressive symptoms at 3 months compared to usual care. Interviews were thematically analysed to identify self‐help strategies and their perceived benefits. Results: Four overarching domains for the self‐management strategies were identified: social, cognitive, behavioural and restorative. Interviewees reported using strategies across multiple domains, which included undertaking enjoyable, immersive activities, that provided relief from automatic negative thoughts and had a perceived cognitive benefit. Differences in the perceived sense of agency were noted around the self‐regulation of mood, which indicated more explicit direction to patient‐identified self‐help management strategies by general practitioners for some may be of benefit in routine care. Conclusion: Some of the reported self‐management strategies aligned with evidence‐based approaches such as physical activity and mindfulness for mental health symptom management. These findings can inform low‐intensity interventions within stepped care models for mental health in primary care, social prescribing models and, help to guide the management of patients by GPs for subthreshold depression.